Computer aided analysis and design of mine transportation systems - Ashton, Andrew R. (1989)
Haulage Costs account for a considerable portion of a surface mine's operational budget. It is therefore vital that, for a particular pit configuration, the optimum utilisation of the available truck fleet is adopted during the mine's life. Also, if the optimisation methods are established beforehand, it is possible to determine exactly how many trucks will be required. Both decisions can be made at the planning stage by the application of linear programming and discrete simulation to computer models of the haulage network.